Otimização do processo de desidratação osmo-convectiva para produção de tomate seco - Bragueto, Graziela (2013)
The tomato (Lycopersicon esculentum Mill.) is a vegetable widely cultivated and consumed worldwide. Plantations of tomatoes intended for processing industry and fresh market. The increasing consumption of tomato can be related to be a versatile food with high nutritional value and can be eaten fresh or processed. Therefore, the aim of this research was to evaluate the processing of dried tomatoes using experimental design to obtain the best conditions and analyze the storage for sixty days seeking a quality product. We used tomato keeper variety of Revelation, in the mature stage, cleaned and cut into two pieces without seeds. After immersed in a solution prepared osmotic with sodium chloride (0 to 10%) and sucrose (3.96 to 46%) for a time from 12.8 to 267.8 minutes. Then, the tomatoes were spread on trays and placed into the dryer at temperatures from 56.6 to 73.4 °C until the moisture adequate visual. There were 17 trials, according to the central composite rotational design 23, which evaluated the effect of three factors in processing: concentration of the osmotic solution, immersion time and drying temperature. After analyzed the quality parameters color and lycopene content, and defined the optimum processing conditions to obtain the maximum, through optimization. From the optimum conditions was carried out further processing the dried tomato, which was stored in two types of packaging for sixty days and analyzed parameters of moisture, color, lycopene and vitamin C. In the drying kinetics of tomato, it was observed that the concentration of the osmotic solution had a significant influence on the moisture loss by reducing the drying time. Among the factors evaluated, the osmotic solution concentration and drying temperature had a significant effect only in the color parameters lightness, chroma index and hue angle. In parameter lycopene, the osmotic solution concentration had a significant effect. The simultaneous optimization of the responses yielded the optimum conditions for processing the dried tomatoes. The process presented overall desirability of 62.43%, and the levels of the factors set out in the following condition: the osmotic solution concentration of 15.5%, soaking time of 12.8 minutes and the drying temperature of 67 ° C. Under these conditions it was possible to obtain dried tomatoes with moisture content of 10.68%, 31.80 brightness, chroma index of 33.20, hue angle of 35.31, lycopene and vitamin C from 144.80 ug / g 4.19 mg/100 g respectively. The dried tomatoes stored for sixty days with air and vacuum packaging, no significant changes in moisture content and vitamin C. In contrast, lycopene has decreased during storage, resulting in loss of intensity and color change detected by the coordinate decrease and increase of C * h *. In addition, there was a reduction in the parameter L *, indicating the darkening of sun-dried tomatoes. Therefore, it was possible to obtain dried tomato quality.